Determinants of Factors Affecting Student Anxiety Preparing a Thesis at Strada Indonesia University - Byba Melda Suhita; Fira Dwi Widiyanik (Universitas STRADA Indonesia, 2024)
The final project is one of the main requirements for a student to obtain a graduation degree. to obtain a graduation degree, where not all students have readiness when facing the final project. facing the final project. some students experience anxiety in compiling a thesis. Compiling a thesis, these factors are, self-efficacy, parental support, peer support, supervisor support.Peer Support, Support of Accompanying Lecturers. This study aims to see factors that influence student anxiety in facing their final Finally. This research method is a quantitative study with a cross This research method is quantitative research with a cross-sectional design, the sample of this study was 150 respondents. Data collection methods using questionnaires and analyzed using Ordinal Regression statistical tests. The results showed that 84 respondents experienced moderate anxiety.